Financing and operational optimization: An example of electric vehicle's major component – Power battery. (October 2020) - Dong, Guoshu; Wei, Lihong; Xie, Jiaping; Zhang, Weisi
Highlights: The dual source financing includes internal financing and external financing. The optimal financing order is not strictly following the pecking order theory under the dual source financing. The effect of initial inventory on external financing depends on the marginal cost. The optimal financing structure has the smallest proportion of external financing. The financing structure can be optimized by reserving more finished product inventory. Abstract: The global awareness of environmental protection, energy conservation, and a country's policy orientation have promoted rapid expansion of electric vehicle (EV) market. A durable and environmentally friendly battery module is the main driving force for EVs. However, the production of an innovative battery core (IBC) and purchase of an ordinary battery core (OBC) require high capital investment. This article takes the battery manufacturer as the research subject and construct a two-stage game model to present his financing and operational strategy with random yield and demand. Deviating from previous studies, we define financing for IBC production as endogenous and the source of funds for IBC's mass production can be either dependent on internal financing alone or in combination with both internal financing and external financing. This study makes three main conclusions. First, the internal financing of inventory resale can not only widen financing channels but also independently control the financing amount and, thus, reduce the loan ratio, which can greatly resolve the financing distress of SMEs. Second, the impact of battery core's cost on capital investment is not monotonous in both internal financing (IF) and dual financing (DF), and surprisingly the increase of OBC's purchase cost in the DF mode may increase the profit of the manufacturer. Third, sufficient internal financing quota does not cause the manufacturer to abandon the use of external financing, they execute internal financing by reselling part of the inventories, and the remaining inventories are used for battery demand. However, this is not completely consistent with the pecking order theory.